STRATEGI PERAWATAN MESIN PULVERIZER MENGGUNAKAN METODE RELIABILITY CENTERED MAINTENANCE DI PT INDONESIA POWER UBP SURALAYA - Juniarti, Anita Dyah; Zakaria, Tatan; Rahmad, Maulvi (Jurnal Intent: Jurnal Industri dan Teknologi Terpadu, 2025)
In the power generation industry, the reliability of machines and equipment is crucial to maintaining a continuous production process. At Suralaya Coal-Fired Power Plant (PLTU Suralaya), one of the critical components in the coal combustion system is the Pulverizer. Based on data from the year 2024, Pulverizer B in Unit 2 recorded the highest number of failures. To address this issue, an analysis was conducted using the Reliability Centered Maintenance (RCM) approach. The RCM stages include Failure Mode and Effect Analysis (FMEA), Logic Tree Analysis (LTA), and Task Selection (TS). The results of the FMEA indicated that the Pyrite System had the highest Risk Priority Number (RPN), with a value of 217. Based on the LTA and TS results, the Pyrite System was categorized as a component that could cause a shutdown, but its failures are still detectable. Therefore, a condition-based maintenance strategy, or Condition Directed Maintenance, was determined to be appropriate. For the Pyrite System, calculations of Mean Time To Repair (MTTR) and Mean Time Between Failure (MTBF) were also conducted, with results showing an MTTR of 2.42 hours and an MTBF of 201.75 hours (approximately 8 days). Additionally, the inspection interval was set at every 188.95 hours (7 days).